Comprehensive pharmacy review - Shargel, Leon;Mutnick, Alan H.;Souney, Paul F.;Swanson, Larry N. (Philadelphia, Pennsylvania : Lippincott Williams & Wilkins, 2013)
The main objective of the book is to provide a comprehensive study guide for pharmacy students and other candidates who are preparing for the North American Pharmacist Licensure Examination (NAPLEX). This volume represents the contributions of more than 50 specialists who provide wide expertise in pharmaceutical science, pharmacy practice, and clinical pharmacy. Their contributions to Comprehensive Pharmacy Review assure that this review guide is accurate and current as well as written in a comprehensible manner for students, teachers, and practitioners alike. This review publication, along with the separate booklet of simulated NAPLEX exams (Comprehensive Pharmacy Review Practice Exams, 8th edition), provides both guidance and test practice for NAPLEX candidates.
Pharmaceutical calculations -- Pharmaceutical principles and drug dosage forms -- Biopharmaceutics and drug delivery systems -- Extemporaneous prescription compounding -- Basic pharmacokinetics -- Bioavailability and bioequivalence -- Biotechnology drug products -- Drug metabolism, prodrugs, and pharmacogenetics -- Pharmacology and medicinal chemistry of drugs affecting the nervous system -- Pharmacology and medicinal chemistry of cardiovascular and diuretic drugs -- Pharmacology and medicinal chemistry of autacoids, nonsteroidal anti-inflammatory drugs, and antihistamines -- Pharmacology and medicinal chemistry of endocrine and related drugs -- Drug-drug and drug-nutrient interactions -- Drug information resources
Includes index.
Keywords: PHARMACY EXAMINATIONS, QUESTIONS, ETC